Letter to the editor concerning the article 'Safety of vaccines administration in hereditary fructose intolerance'. Issue 8 (3rd August 2021) - Saborido-Fiaño, Rebeca; Martinón-Torres, Nazareth; Crujeiras-Martinez, Vanesa; Couce, Maria Luz; Leis, Rosaura
ABSTRACT: The most important approach for the management of hereditary fructose intolerance is a strict avoidance of fructose, sucrose and sorbitol from the diet and medications. A safe threshold of 2.4 mg/kg/dose was recently established by the Instituto Superiore di Sanità of Italy for both oral and parenteral routes, thus shouldering a safe administration of a majority of vaccines in these patients. This would not include, Rotarix® pre-established oral suspension and Rotateq® vaccines, which are indeed contraindicated. Moreover, Rotarix® white powder and solvent for oral suspension would only be safely administered at a weight above 9.3 kg. Overall, these recommendations to avoid rotavirus vaccination are difficult to implement because these vaccines are given during exclusive breastfeeding, prior to fructose-containing food introduction.